Tetralogy of Fallot with subarterial ventricular septal defect: Surgical outcome in the current era - Vimalarani Devendran; Prakash R Anjith; Anil Kumar Singhi; Vimala Jesudian; Ejaz Ahmed Sheriff; Kothandam Sivakumar; Roy Varghese (Wolters Kluwer Medknow Publications, 2015)
Background: Tetralogy of Fallot (TOF) with subarterial ventricular septal defect (VSD) is more common among Asians than Caucasians. Compared with the regular subaortic VSD postoperative right ventricular outflow obstruction is more common because of the sub-pulmonary extension of the defect. The objective of this study is to analyze the surgical implications and outcomes of patients with TOF - subarterial VSD in the current era. Patients and Methods: In all, 539 consecutive operated patients with TOF from May 2005 to September 2012 were retrospectively reviewed. Eighty-five patients had subarterial VSD. Seventy-nine of these underwent intracardiac repair. Preoperative clinical, echocardiographic features, operative and postoperative variables were assessed. Results: The median age at surgery was 6 years and the median weight was 14 kilograms. The male to female ratio was 1.7:1. TOF with subarterial VSD was associated with frequent use of transannular patch (74.6%). The early mortality was 2.5%. Follow up was 92% complete with a mean duration of 20 months with actuarial survival of 97.3% at 5 years. Two patients required reoperation for significant right ventricular outflow tract obstruction (RVOTO) at one year and three years, respectively. Conclusions: Intra cardiac repair for TOF with subarterial VSD has low perioperative mortality and morbidity. Transannular patch augmentation of the right ventricular outflow tract (RVOT) is required in a significant proportion of these patients. Precise suturing of the VSD patch, adequate infundibular resection and lower threshold for a transannular patch placement ensures a smooth early postoperative recovery.